Do Cochrane summaries help student midwives understand the findings of Cochrane systematic reviews: the BRIEF randomised trial. Issue 1 (December 2016) - Alderdice, Fiona; McNeill, Jenny; Lasserson, Toby; Beller, Elaine; Carroll, Margaret; Hundley, Vanora; Sunderland, Judith; Devane, Declan; Noyes, Jane; Key, Susan; Norris, Sarah; Wyn-Davies, Janine; et al.
Abstract Background Abstracts and plain language summaries (PLS) are often the first, and sometimes the only, point of contact between readers and systematic reviews. It is important to identify how these summaries are used and to know the impact of different elements, including the authors' conclusions. The trial aims to assess whether (a) the abstract or the PLS of a Cochrane Review is a better aid for midwifery students in assessing the evidence, (b) inclusion of authors' conclusions helps them and (c) there is an interaction between the type of summary and the presence or absence of the conclusions. Methods Eight hundred thirteen midwifery students from nine universities in the UK and Ireland were recruited to this 2 × 2 factorial trial (abstract versus PLS, conclusions versus no conclusions). They were randomly allocated to one of four groups and asked to recall knowledge after reading one of four summary formats of two Cochrane Reviews, one with clear findings and one with uncertain findings. The primary outcome was the proportion of students who identified the appropriate statement to describe the main findings of the two reviews as assessed by an expert panel. Results There was no statistically significant difference in correct response between the abstract and PLS groups in the clear finding example (abstract, 59.6 %; PLS, 64.2 %; risk difference 4.6 %; CI −0.2 to 11.3) or the uncertain finding example (42.7 %, 39.3 %, −3.4 %, −10.1 to 3.4). There was no significant difference between the conclusion and no conclusion groups in the example with clear findings (conclusions, 63.3 %; no conclusions, 60.5 %; 2.8 %; −3.9 to 9.5), but there was a significant difference in the example with uncertain findings (44.7 %; 37.3 %; 7.3 %; 0.6 to 14.1, p  = 0.03). PLS without conclusions in the uncertain finding review had the lowest proportion of correct responses (32.5 %). Prior knowledge and belief predicted student response to the clear finding review, while years of midwifery education predicted response to the uncertain finding review. Conclusions Abstracts with and without conclusions generated similar student responses. PLS with conclusions gave similar results to abstracts with and without conclusions. Removing the conclusions from a PLS with uncertain findings led to more problems with interpretation.